KEDUDUKAN HADITH DALAM BUKU "DOA-DOA MUSTAJAB HARIAN" YANG DI PETIK DARIPADA HADITH DAN AL-QURAN: KAJIAN TAHRIJ HADITH - Shafie, Nor Bazila; Nazri, Mohd Arif (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2017)
Takhrij is an important method in science of hadith and one of the methodology used by hadith scholar to determine the position ofhadith issued to know the source and the status of hadith either maqbul or mardud. There are 101 dua? from hadith found, with unknown specified source and status. The objective of this research is purposely to reveal both the validity and to rereview the status of hadith by takhrij means. The methodology used for this research are qualitative by analyzing each hadith with referring to original and authorised scriptures in order to determine the authentic  sources as well as status of the hadiths. In conclusion, 52% of the hadiths consist of hadiths maqbul, while 47% of hadiths are mardud, the rest 2% are irrelevent. This study provides contribution for hadith researchers and communities in practising the daily dua? sourced authentic hadith.